Design of substrate integrated waveguides based on nanowires: Numerical guidelines - Van Kerckhoven, Vivien; Piraux, Luc; Huynen, Isabelle (International journal of numerical modelling, 2021)
A thorough study of the parameters influencing the operation of devices based on nanowired alumina substrate is presented. The basic structures are realized by growing metallic nanowires inside alumina porous substrate. The control of the areas wherein growth occurs allows building of various microwave devices supported on the filled template. The performances of these devices depend on the material parameters and topology/geometry in presence. These devices have the particularity to combine nanoscale, through the use of nanowires, and millimeter scale that is characteristic of microwave devices and their associated operating wavelength. The gap between the two‐scale ranges implies that analytical models and numerical simulation tools have to be combined to modelize and design performant microwave devices, such as Nanowired Substrate Integrated Waveguides (NSIWs) devices that are the subject of the paper. A deep parametric analysis of the properties and operation of the basic NSIW is presented and is followed by the illustration of two designs: a simple NSIW line, and an EBG NSIW filter.